The Production of Charcoal from Bamboo, Coconut Shell, and Palm Shell as Activated Carbon - Bigat, Sylvester; AWANG, ZARIZI (Progress in Engineering Application and Technology, 2021)
The activated carbon filter is efficient in removing organics such as unwanted taste and odor. That organics matter including micropollutants, chlorine, and fluoride from drinking water or wastewater. The activated carbon filtration is commonly used in treatment plants center and households. This activated carbon aims to produce drinking water and is used in industries to treat effluents. In this research, the raw material from bamboo, coconut shell, and palm shell was used to prepare the activated carbon (AC). The AC preparation will be completed through the primary process that includes the carbonization process and the sieving process. After that, the secondary process of producing activated carbon by chemical activation process using sodium chloride (NaCl). The AC was evaluated in terms of ph value, total dissolved solids, electrical conductivity, and absorption efficiency. The absorption efficiency will be observed by discoloring of methylene blue solution using activated carbon from each material. It is expected that the use of natural resources such as coconut shell, bamboo, and palm shell as AC can achieve higher absorption efficiency, more stable, and cheaper compared to the existing market.